P1552CAN WE GET ADEQUATE DIALYSIS WITH LIQUID AT 300 ML/MIN ?. (6th June 2020) - Barril, Guillermina; Sobrino, Pedro; Giorgi, Martin; Nuñez, Almudena; Santos, Begoña; Pascual, Natalia; Sanz, Pilar; Cano, Francisco; Nogueira, Angel; Sanchez Tomero, Jose Antonio
Abstract: Background and Aims: The portable HD monitors achieve a good adaptation with HD dialysate at 200ml / min using the concept of saturation of the HD dialysate. We decrease from 800ml / min to 500ml / min with good adaptation some years ago. To assess the effectiveness of HD in both HD-standard and HDF-online with dialysate flow at 300ml / min by establishing approximate mathematical model of clearance. Methods: We conducted an HD session with dialysate flow at a speed of 300ml / min, half week session to 52 patients in our unit. We value vascular access, session time, liters of blood-purified and total infusion in HDF online. We review HD monitor and dialyzer. We perform pre and postHD blood determinations: Urea, B2microglobulin, P and uric acid, assessing urea reduction rate (PRU), b2microglobulin reduction rate (PR2microg) with both dialysate flows at 300ml / min and 500ml / min. We also have evaluated the differences between the two methods. In the HD dialysate flow we determine at 300ml / min at 5, 10, 30, 45 and 60min (total dialysate collection in the first hour with sample of the mixture) urea, B2microg, Uric acid and P and at 2, 3 and 4 hours establishing a mathematical model with an approximation curve in both HD and online HDF. Results: Five patients in standard HD (4h), 35 HDF online (4h) (x Liters infused 24.87 ± 2.79 l) and 12 short-daily HD (2h30min). 18 catheter and 34 FAV. Xliters purified blood = HD daily 54.41 ± 5.63l, HD standard 87.38 ± 6.01 and HDFonline 82.02 ± 16.13l. The xPRU = 76.17 ± 10.49%, PRB2microg = 73.82 ± 13.49, Kt / V = 1.52 ± 0.28. By scheme at 300ml / min of HD fluid flow: HDFonline xPRU = 81.54 ± 5.25, Standard HD = 78.01 ± 3.03, Daily HD = 60.19 ± 6.71; xPRb2microg HDFonline = 76.70 ± 14.76%, Standard HD 65.44 ± 11.81, Daily HD = 69.16 ± 6.49. Comparing the xPRU at 300ml / min of liquid vs 500ml / min we didn´t found significant differences, nor in the x preHD of urea and B2microglobulin. With the dialysate samples we obtain a polynomial model of order 7 allowing cuantitative adjustment of the curve.R2 0.9, observing in the first 2 hours the greater removing. Conclusions: 1. The results are sufficient to consider the result of the removing in each scheme adequate. 2. The decrease in costs would be important (40% of water + energy saving and longer duration elements water treatment. 3. Further study are necessary.